Rainfall-runoff data from an urban catchment in Luleå, Sweden. - Broekhuizen, Ico; Leonhardt, Günther; Viklander, Maria (Zenodo, 2020)
Description and map of the catchment: Broekhuizen, Ico, Günther Leonhardt, Jiri Marsalek, and Maria Viklander. “Event Selection and Two-Stage Approach for Calibrating Models of Green Urban Drainage Systems.” Hydrology and Earth System Sciences 24, no. 2 (February 26, 2020): 869–85. https://doi.org/10.5194/hess-24-869-2020. Rain gauge: Geonor T200B weighing bucket . Alter-type wind shield. Flow gauge: Teledyne ISCO 2150 Area-Velocity: acoustic Doppler for flow velocity, pressure transducer for water level. Additional information on field calibration checks of the rain gauge and laboratory testing of the same type of flow sensor: Broekhuizen, Ico. “Uncertainties in Rainfall-Runoff Modelling of Green Urban Drainage Systems: Measurements, Data Selection and Model Structure.” Licentiate thesis, Luleå University of Technology, 2019. http://urn.kb.se/resolve?urn=urn:nbn:se:ltu:diva-73367. Notes: - The observations in this data set cover the snow-free parts of 2016-2019. - For flow data, only observations >= 1 l/s are provided. The authors would like to thank Helen Galfi, Ralf Rentz and Karolina Berggren for their work in the initial setup and maintenance of the field measurements.